The Influence of Electronic Word of Mouth (E-WOM) and Consumer Trust on Purchase Decisions in the Shopee Marketplace Among Generation Z - Efti Novita Sari; Aryadi Aryadi; Nana Sari; Habibah Tun Nisyah; Agung Gunawan (Journal of Financial and Business, 2026)
the rapid growth of e-commerce has changed consumer purchasing behavior, particularly among generation z, who rely heavily on digital information before making purchasing decisions. electronic word of mouth (e-wom) and consumer trust have become two important factors influencing online purchasing behavior in marketplace platforms. this study aims to examine the influence of electronic word of mouth (e-wom) and consumer trust on purchase decisions in the shopee marketplace among generation z. this research employed a quantitative approach with an explanatory research design. data were collected through an online survey using a structured questionnaire distributed to generation z consumers who had previously made purchases through shopee. the sampling technique used was purposive sampling, and the data were analyzed using multiple linear regression analysis. the findings reveal that electronic word of mouth (e-wom) has a positive and significant effect on purchase decisions. likewise, consumer trust positively and significantly influences purchase decisions and emerges as the more dominant factor in shaping consumers' purchasing behavior. these findings indicate that although generation z actively uses online reviews, ratings, and recommendations as sources of information, their purchasing decisions are largely determined by their level of trust in the marketplace and sellers. this study contributes to the literature on digital consumer behavior and provides practical implications for e-commerce platforms and online sellers in developing strategies to improve consumer trust and effectively manage electronic word of mouth in order to encourage purchasing decisions.